Molecular‐Switch‐Embedded Solution‐Processed Semiconductors. Issue 4 (23rd November 2022) - Yu, Seong Hoon; Hassan, Syed Zahid; So, Chan; Kang, Mingyun; Chung, Dae Sung
Abstract: Recent improvements in the performance of solution‐processed semiconductor materials and optoelectronic devices have shifted research interest to the diversification/advancement of their functionality. Embedding a molecular switch capable of transition between two or more metastable isomers by light stimuli is one of the most straightforward and widely accepted methods to potentially realize the multifunctionality of optoelectronic devices. A molecular switch embedded in a semiconductor can effectively control various parameters such as trap‐level, dielectric constant, electrical resistance, charge mobility, and charge polarity, which can be utilized in photoprogrammable devices including transistors, memory, and diodes. This review classifies the mechanism of each optoelectronic transition driven by molecular switches regardless of the type of semiconductor material or molecular switch or device. In addition, the basic characteristics of molecular switches and the persisting technical/scientific issues corresponding to each mechanism are discussed to help researchers. Finally, interesting yet infrequently reported applications of molecular switches and their mechanisms are also described. Abstract : Under the banner of "More than Moore, " the key to developing solution‐processed semiconductor‐based optoelectronic devices is to add additional functionality to a limited space. Molecular switches can induce transitions between metastable isomers by non‐destructive stimuli, effectively amplifying the functionality of optoelectronic devices when embedded in semiconductors. This review categorizes and discusses molecular‐switch‐embedded optoelectronic devices according to their operating mechanisms.